2022
DOI: 10.21203/rs.3.rs-2401638/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CUX1-related neurodevelopmental disorder: Deep insights into phenotype-genotype spectrum and underlying pathology

Abstract: Heterozygous, pathogenic CUX1 variants are associated with global developmental delay or intellectual disability. This study delineates the clinical presentation in an extended cohort and investigates the molecular mechanism underlying the disorder in a Cux1+/− mouse model. Through international collaboration, we assembled the phenotypic and molecular information for 34 individuals (23 unpublished cases). A Cux1+/− mouse model was used to analyze CUX1 expression in the brain and evaluate susceptibility to epil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…GMDB-FAIR has been used to develop many NGP approaches 19,[35][36][37] for predicting rare disorders after the first usage in GestaltMatcher in 2022. Moreover, GMDB-FAIR data can be used in the research platform (Supplementary Note) to validate the results shown in the published works [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] that provides transparency to the researcher using GestaltMatcher and the probability to extend the existing research with the user's additional data.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…GMDB-FAIR has been used to develop many NGP approaches 19,[35][36][37] for predicting rare disorders after the first usage in GestaltMatcher in 2022. Moreover, GMDB-FAIR data can be used in the research platform (Supplementary Note) to validate the results shown in the published works [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] that provides transparency to the researcher using GestaltMatcher and the probability to extend the existing research with the user's additional data.…”
Section: Discussionmentioning
confidence: 65%
“…For example, Ebstein et al showed that facial dysmorphism was heterogeneous among the entire PSMC3 patient cohort, but facial similarities were found in patients sharing the same pathogenic variants 39 . To date, 15 publications have analyzed the facial phenotype of the cohort with the GMDB-FAIR dataset and GestaltMatcher [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] . All results can be reproduced in the research platform of GMDB, which we introduce in the Methods section (Figure 2c, Figure 3c and Supplementary Note).…”
Section: Gmdb-fair Dataset Drives the Advancement Of Ngp Technologymentioning
confidence: 99%
“…These include motifs for TRPS1, ZNF652, and CUX2 (Figure 6F). CUX1 and CUX2 are homeodomain TFs that control dendritic branching, spine morphology, and synapse formation 87,88 . Together, these findings provide a comprehensive view of the transcriptional landscape within this withdrawal-associated subpopulation of D1 MSNs, highlighting the molecular mechanisms and regulatory networks that govern the unique adaptations observed during prolonged withdrawal from chronic cocaine.…”
Section: Transcriptional Dynamics In a Cocaine Withdrawal-associated ...mentioning
confidence: 99%
“…For example, Ebstein et al showed that facial dysmorphism was heterogeneous among the entire PSMC3 patient cohort, but facial similarities were found in patients sharing the same pathogenic variants 34 . Deploying this method within our research platform has facilitated the quantification of similarity across 18 cohorts, with 15 already published 34,[44][45][46][47][48][49][50][51][52][53][54][55][56][57] .…”
Section: Facilitating Ngs Analysis With the Gestaltmatcher Api And Re...mentioning
confidence: 99%